Education as Hermeneutic Study: Uncovering Meaning in The Digital Era - Faridah, Faridah; Nurhayati, St. (Jurnal Riset dan Inovasi Pembelajaran, 2025)
This objective study explores the role and challenges of hermeneutics in education in the modern digital era. This type of research uses a systematic literature review approach to studies published between 2017 and 2024. This article uses strict criteria for what to include and what to leave out to look at the main trends in how hermeneutics is being used in social media, AI, and big data. It also talks about the ethical and philosophical problems that come up. These main results show that using hermeneutics in education in the digital age can help students understand texts better, but it can also cause problems with ethics, meaning, and how to represent different cultures. Additionally, in hermeneutics, interpretation constitutes the essence of comprehension. This perspective is appropriate for educators, as their responsibility is to comprehend human behavior and creations and subsequently impart this understanding to students in the learning process. The results of this SLR show how important it is to use a more integrated hermeneutical approach to deal with the problems and opportunities of using digital technologies in education. They also recommend further research on developing flexible and situation-relevant interpretation methods to promote a more balanced relationship between education, technology, and society.